Importance and Characteristics of Administrative Documents (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article analyzes the specific features of the administrative document. The characteristics of the administrative document, its entry into force, types, and other aspects different from other documents are analyzed.